WRITING IN MANGGARAIAN: AN ANALISIS OF A TERTIARY STUDENTŚ TEX - TANS FELIKS (Program Magister Linguistik Universitas Udayana, 2008)
Abstract A study conducted at Nusa Cendana University in March 2007 aims at finding out how a Manggaraian text by Apas, a student, is structured. The data are analyzed descriptively. It is found that the overall structure of the text is good. Yet, it lacks details; its introductory and concluding paragraphs are poor; its word choice is heavily influenced by Indonesian and English; some sentences and paragraphs are poorly structured; some words are incorrectly spelt; and, some punctuation is false. It is suggested that Apas improve his ability on such cases and that the Government of Indonesia and linguists interested in Manggaraian standardize its grammar.